A morte na Unidade de Terapia Intensiva: o agir e o sentir do profissional de saúde - NINA, Rachel Vilela de Abreu Haickel (2013)
Death is a natural process intrinsically linked to life that brings different emotions and meanings, and in recent decades has moved from the familiar environment for the hospital environment, adding a burden of loneliness and negativity that caused her to be transformed into a subject rarely discussed among health professionals. In the training of nurses and doctors death and dying has been shalowed treated and the students have contact with them at specific times and increasingly rare during their training. At the end of their graduation, when faced with the finitude of their patients feelings of failure, anxiety and helplessness may arise, and even cause illness in these professionals. In ICU death is part of their daily lives, it is the place of occurrence of the majority of hospital deaths. The ICU is the space for specialized treatment where technology and training unite to address clinical situations where the threat to life is always present, and thus prolong the dying indefinitely many times. The treatment of these conditions requires the professional to a need to focus on the disease, making him forget and even deny that the human body threatened by the imminence of death. Transformed into an enemy, death is fought at all costs, and during this battle the relationship between professional and patient/family is lost. Aiming to analyze factors associated with the perception of the meaning and attitudes toward death held a study with quantitative and qualitative methods of research. With the quantitative methodology performed a crosssectional study, analytical professional with the four ICUs of a university hospital between August 2010 and August 2012 in which we considered five different outcomes: meaning of death ";" meaning of the patient's death terminal ";" attitude at the news of the death "; "resuscitation of the patient without therapeutic possibility "," discussion of non-resuscitation order ", we used Poisson regression and multinomial logistic (alpha = 5%) to estimate associations. Through questionnaires and semi-structured interviews with professionals from pediatric intensive care, we used qualitative methodology with analysis of the thematic content. Results: there were 118 professionals working in the ICU during the study, 97 were included in this research , and of these 14 were the sample of qualitative methodology. had 52 doctors and 45 nurses whose age ranged from 24 to 62 years (M = 38 ± 7.6), 77.32% were female, aged 27-53 years, the time in the ICU ranged from 1 to 32 years and who worked on average 43 hours weekly. meaning of death varied according to the professional category, type of ICU and weekly workload. Regarding attitude to death news and nurses and those who had weekly workload greater than 60 h share the communication, who said to have their behavior at the news of death to be influenced by education and nurses agreed with the resuscitation of the patient terminal; professionals with over 38 years working in ICU children agreed that the DNR should be discussed. Among those who worked with children a sense of ambivalence about the situation of death was related to the clinical condition and the context in which it took that child. Anxiety, emotion very present among these professionals can arouse guilt and helplessness demonstrating the complexity involved in the perception of death. They use religion as a coping mechanism and recognize the lack of preparation during undergraduate and postgraduate. In conclusion we sought that the feeling was associated with workload weekly professional category and type of ICU in which they work, while the act was associated with vocational training and category, in relation to the death of children, this arouses mixed feelings in health professionals, who use the religion and involvement Family to face it and resent the lack of contact with the subject during their training.